2009
DOI: 10.9773/sosei.50.868
|View full text |Cite
|
Sign up to set email alerts
|

Thin-Sheet-Metal Bending by Laser Peen Forming with Femtosecond Laser

Abstract: A femtosecond laser is a type of ultrashort-pulse laser. Femtosecond laser irradiation induces high-pressure plasma and shock waves at the surface of a target. Under some irradiation conditions, such shock waves are enough to deform the target plastically. Laser peen forming is a type of sheet metal forming using this deformation by shock waves. The author adopted laser peen forming using femtosecond laser for thin-sheet-metal bending. Generally, shock waves induced in air are much smaller than those induced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
3
0
3
Order By: Relevance
“…Ocana et al [5] presented the influence of process parameters on the net bending angle of thin sheet metals. Sagisaka et al [6,7] showed the changes of bending property with atmosphere, process parameters and elastic pre-bending on pure aluminum thin sheets. Hu et al [8,9] discussed the bending capability of thin sheet metals, residual stress distributions and the microstructure close to their opposite sides.…”
Section: Introductionmentioning
confidence: 99%
“…Ocana et al [5] presented the influence of process parameters on the net bending angle of thin sheet metals. Sagisaka et al [6,7] showed the changes of bending property with atmosphere, process parameters and elastic pre-bending on pure aluminum thin sheets. Hu et al [8,9] discussed the bending capability of thin sheet metals, residual stress distributions and the microstructure close to their opposite sides.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Therefore, peening without a sacrificial overlay under atmospheric conditions is considered to be possible using a femtosecond laser pulse. Femtosecond laser peening of steel under water 20,21 and femtosecond laser peen forming of thin metal sheet in the air 22,23 have been reported. However, femtosecond laser peening without a sacrificial overlay under atmospheric conditions aiming to improve mechanical properties has never been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Fale uderzeniowe stosowane do kształtowania przez laserowe młotkowanie (laser peen forming) są wytwarzane za pomocą impulsów nano-, piko-i femtosekundowych, z użyciem lub bez dodatkowej warstwy absorpcyjnej [8][9][10][11]. Ta nowa metoda gięcia folii i blach cienkich jest analizowana pod kątem jej zastosowania w produkcji przyrządów medycznych, sprzętu elektronicznego [11] i ramion zawieszenia głowicy magnetycznej dysku twardego.…”
unclassified
“…Bez wykorzystania wstępnego naprężenia ujemne kąty gięcia można otrzymać po obróbce femtosekundowymi impulsami laserowymi [7,9]. Ta metoda wymaga jednak stosunkowo długiego czasu obróbki, ponieważ deformacja powstaje w wyniku skanowania przedmiotu obrabianego wiązką laserową i akumulacji efektów wielu impulsów.…”
unclassified
See 1 more Smart Citation